Adsorption of epoxy oligomer ED-20 and structure interfacial layer on the glass surface - A. N. Trofimov; O. Y. Bryksina; V. M. Komarov; V. S. Kopytin; G. A. Simakova; I. D. SimonovEmeljanov (Тонкие химические технологии, 2009)
Adsorption of epoxy oligomer ED-20 on the glass surface have investigated. Comparison experimental and calculated on basis Landau-Lifshits theoretical model results indicated that adsorption in studied system was polymolecular.